ダイ8ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1967～1968 - 鳥居, 鉄也; トリイ, テツヤ; TORII, Tetsuya (国立極地研究所, 1968)
P(論文) The 8 th Japanese Antarctic wintering party led by Dr. T. TORII consists of 24 members, of which 14 are scientists and the rest logistics supporters. The party was organized succeeding the 7th wintering party, with its project centered on aeronomy andbiology. Items of obseivation are as follows cosmic rays, aurora and aiiglow, lonospheie, atmospheric emissions over a wide range of radio frequencies (ELF, VLF, LF, RF), geomagnetism, meteorology, natural earthquake, biology, glaciology, geomorphology, geochemistry, etc. Construction for the second year after the renovation of Syowa Station included 5 buildings aeronomy laboratory, mess hall, balloon inflation shed, garage and air traffic control building. Keeping pace with the improvement of facilities at the base, consumption of water has increased. Unfortunately, a break developed in a small reservoir, so that the water supply for the summer season was dependent on puddles on sea ice around the base. Electric power was supplied by a separate 20KVA generator for scientific instruments in order to prevent electric noise, and the 45KVA generator was used for general purposes. Shortage in power supply suggested the need for installation of another generator. Two field trips were made to the foreign stations. One trip was to Molodezhnaya Station from August 17 through September 2, 1967. The trip, which covered the course along the east Prince Olav Coast, was designed for observation of gravity, geomorphology, glaciology, biology and geochemistry. The other inland traverse was undertaken from November 5, 1967 through January 15, 1968. The course ran along the longitude 43°E to latitude 75°S and then direct to Plateau Station, having carried out the observation of meteorology, glaciology, geomorphology, geomagnetism and geochemistry. VLF observation was not performed because of a trouble in machinery. The party returned to the base by the same route. Cooperation and help extended by the U. S. A. and USSR parties during the field trips are gratefully ...